PENINGKATAN KUALITAS PEMBELAJARAN BERBASIS TEKNOLOGI VIRTUAL REALITY DI SMA SANTA URSULA - Nurhasanah Siregar; Maria Magdalena Melina; Pretty Nurwhite Tika; Supriyatin Supriyatin (Universitas Lancang Kuning, 2023)
Learning media is one of the keys to successful learning in the classroom by improving learning activities to be more effective and efficient. Now the development of learning media is increasingly advanced thanks to advances in information technology. One of the information technology-based learning media that is currently widely used is Virtual Reality. The utilization of Virtual Reality learning media is very appropriate to use in classroom learning that needs to present real examples so that students can understand the material, so as to improve the quality of learning. The purpose of this study is to analyze how to improve the quality of learning based on Virtual Reality technology at Santa Ursula Senior High School Jakarta. The method used is descriptive quantitative research method with data collection techniques in the form of questionnaires, interviews, observations, and documentation studies. The results showed that the use of Virtual Reality can improve the quality of learning in several subjects. The use of Virtual Reality has a positive impact on learning activities, such as learning to be more varied, fun, and interesting. In addition, students' interest in learning in class also increases, because they want to be actively involved in the learning process. However, the use of Virtual Reality at Santa Ursula Senior High School Jakarta is still not optimal. This is because there are still many teachers who are not mature in preparing the use of Virtual Reality media in learning, so the use of Virtual Reality has not been evenly distributed in all classes.